The Role of Zakat, Waqf, and Islamic Business in Sustainable Economic Development: A Review of Funding and Fund Provision Models - Siti Nurhaliza; Seli Sukma Anggraini; Febi Bonita; Dini Imeliani; Melati Luniagus; Muhammad Nafiscal Farih (CV. Doki Course and Training, 2025)
This research aims to determine and comprehen about zakat and waqf role in the economic development of the Muslims (Ummah) in Islamic economic perspective. Research types is library research. Research approach using combination of a philosophical and phenomenological approach. A philosophical approach is used to look deeply at philosophical material objects such as values, principles, Islamic economic goals and zakat and wakaf role in Muslims (ummah) economic development. While the phenomenological approach is used to look at the economic development that is reflected in society through statistical data about poverty, as well as those contained in a literature work such as books, documents, scientific works and research. Study result: Islamic economic system aims is to improve society welfare and to realize maqasid as sharia, and uphold justice value, therefore the important base of zakat and waqf distribution is Allah guidance in Qur’an Surah (chapter) [59]: 7